BALANCING EXPLOITATION & EXPLORATION: AN AMBIDEXTROUS ORGANIZATION FRAMEWORK IN THE DIGITAL TRANSFORMATION PROCESS OF BANK PEREKONOMIAN RAKYAT (BPR) SARIDANA SURABAYA - Alvian Susanto; Aurik Gustomo (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to create a workable framework and to determine the optimal strategic priority for the digital transformation of rural banks (traditionally known as Bank Perekonomian Rakyat) in Indonesia amidst the disruptive competition from the fintech and digital banking, and the chronic resource constraints. Based on the Ambidextrous Organization Theory, this research utilizes a mized-methods approach, combining qualitative thematic analysis & value focus thinking derived from executive interviews & survey, with the quantitative Analytic Hierarchy Process to evaluate the digital product alternatives against foundantional organizational criteria. The analysis reveals that shareholder willingness and business potential are the most dominant criteria driving digital adoption, superseding technological and capital limitations, while Consumer Lending emerges as the to priority product alternative, outperforming other alternatives such as retail funding and fee-based services. In conclusion, successful digital transformation for resource-constrained financial institutions depends fundamentally on leadership mindset and market pragmatism rather than investment on technological infrastucture. Rural banks must adopt an ambidextrous operational model, and prioritizing symbiotic integrations with existing financial technology ecosystems to disburse rapid, revenue-generating consumer loans. This targeted approach secures the immediate financial returns necessary to sustain ongoing digital transformation while deliberately maintaining traditional offline processes for complex loan financing.